2008
DOI: 10.1136/ard.2007.084947
|View full text |Cite
|
Sign up to set email alerts
|

Pathological features of temporal arteries in patients with giant cell arteritis presenting with permanent visual loss

Abstract: Giant cells are strongly associated with PVL, with a significant gradient between great risk and large number of giant cells. However, PVL was neither associated with the intensity of the inflammatory infiltrate, nor with the presence of arterial thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 22 publications
1
46
1
5
Order By: Relevance
“…In an early series of 90 cases from neurology and ophthalmology clinics, up to 60% of patients presented with permanent loss of vision attributable to either ischaemic papillopathy or retinal artery occlusion; 23 other cases presenting primarily to physicians demonstrated a much lower risk of sight loss of 7.4% to 19.1%. [24][25][26][27] The risk of sight loss associated with GCA has fallen 28 There is a small but significant risk of stroke, highlighted as possibly being between 2.8% and 6% in two recent studies. 29,30 Therefore, an early diagnosis and initiation of immunosuppressive treatment with high doses of steroids is required, making the condition a medical emergency.…”
Section: Clinical Presentation Of Giant Cell Arteritismentioning
confidence: 99%
“…In an early series of 90 cases from neurology and ophthalmology clinics, up to 60% of patients presented with permanent loss of vision attributable to either ischaemic papillopathy or retinal artery occlusion; 23 other cases presenting primarily to physicians demonstrated a much lower risk of sight loss of 7.4% to 19.1%. [24][25][26][27] The risk of sight loss associated with GCA has fallen 28 There is a small but significant risk of stroke, highlighted as possibly being between 2.8% and 6% in two recent studies. 29,30 Therefore, an early diagnosis and initiation of immunosuppressive treatment with high doses of steroids is required, making the condition a medical emergency.…”
Section: Clinical Presentation Of Giant Cell Arteritismentioning
confidence: 99%
“…On the other hand, one study (60) showed an increased frequency of visual ischemic events in patients with ESR values ranging between 70 and 100 mm/h at the time of disease diagnosis. Similarly, another survey (63), found no increased risk of visual loss or other cranial ischemic events in patients with low ESR (< 40 mm/h). Histologically, the presence of giant cell cells has been associated with increased risk of visual loss (64), but this finding needs to be confirmed.…”
Section: Ophthalmologic Manifestationsmentioning
confidence: 88%
“…GCA with normal ESR has, however, been reported (175,176,177), even in patients with visual disturbances (176,178) and devastating central nervous system complications (179). Interestingly, when patients with GCA and normal ESR were followed-up, these patients were never able to mount a high ESR during subsequent episodes of inflammation caused by infection which may imply a genetically determined blunted cytokine response to inflammation (63). ESR and CRP are relatively lower in patients with occult GCA according to some observations (14).…”
Section: Laboratory Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Autoren weisen jedoch ausdrücklich darauf hin, dass die Immunhistochemie nicht dem Ziel dienen sollte, eine eigentlich negative Biopsie zwanghaft der klinischen Erwartung einer Riesenzellarteriitis anzunähern. Zudem besteht in der Literatur kein Konsens bezüglich der Frage, ob nun die Dichte und die Zusammensetzung des Entzündungs-zellinfiltrates mit dem klinischen Schweregrad oder den laborchemischen Verän-derungen der Riesenzellarteriitis korrelieren [2,16].…”
Section: Histologische Diagnosekriterienunclassified